Analysis of the need to develop socrates dialogue learning design using the moral dilemma method - Ana Dwi Wahyuni; Fiena Saadatul Ummah; Mochamad Nursalim (Jurnal Bidang Pendidikan Dasar, 2026)
This study aims to analyze the need for developing a Socratic Dialogue learning design using the Moral Dilemma Method in Pancasila Education subjects to instill the value of tolerance and minimize bullying behavior in elementary schools. The study uses a qualitative case study approach. Data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis follows an interactive model in the form of data reduction, data presentation, and drawing conclusions. The results of the study show: (1) Pancasila Education learning is still dominated by conventional approaches that are ineffective in preventing bullying; (2) Students' understanding of the value of tolerance is still partial and often wrong (considering bullying as a "joke"); (3) Teachers have difficulty in facilitating discussions and conflict resolution; and (4) There is an urgent need for contextual participatory learning with students' social dynamics.